Age-related Correlations of Telomere Length of Predator Fish Muscle Tissues with Potentially Different Ageing Mechanisms - Mikhailova, M.V.; Zolotarev, K.V.; Mikhailov, A.N.; Nakhod, V.I.; Voronko, O.E.; Zhdanov, D.D.; Archakov, A.I. (Biomedical Chemistry: Research and Methods, 2024)
The mechanisms of aging differ and have their own features both mammals, and in different species groups of fish. Telomere length is an indicator of the theoretical number of cell cycles that cells of a particular tissue can go through; therefore, the age-related dynamics of telomere length characterizes changes in the tissue's ability to regenerate and is necessary to describe the mechanism of tissue aging. In this work, age-related linear regressions of the telomere lengths of muscle tissue of northern pike (Esox lucius) and zander (Sander lucioperca) were empirically obtained for the wide age groups of individuals of both sexes. The identified significant difference in the dependences on their slope values indicates different degrees of decrease in the ability to regenerate muscle tissue with age, which is consistent with the previously discovered physiological characteristics of the muscle tissue of pike. In both fish species studied, telomere length in females decreases with age much more slowly than in males, which is a common feature in the aging mechanisms of most vertebrates.